Effect of Physical Activity Level and Physical Fitness Level on Motor Students MTs Negeri 1 Banyumas - roni, Ahmad Sya'roni; Rahayu, Setya; Rumini, Rumini (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2021)
The problem in this study is the low level of physical activity of students, as well as the level of physical fitness that students do not have. This research focuses on; (1) analyze and look for the influence of the student's level of physical activity and the student's physical fitness level on the student's motor level. This research is a mixed methods research. The subjects of this study were all students of Mts Negeri 1 Banyumas, using observation data collection techniques, questionnaires and documentation. Data analysis technique using anava statistic with significance α ≤ 0.05. The results showed: (1) Physical activity of MTs Negeri 1 Banyumas students in medium theories, with an average score of 2.36; (2) Physical fitness of students of MTs Negeri 1 Banyumas in good theories, with an average score of 18.5; (3) Motor skills of MTs Negeri 1 Banyumas students in good theories, with an average score of 20.21; (4) the influence of physical activity on the motor skills level of students of MTs Negeri 1 Banyumas F-count of 0.021 < 0.05; (5) the influence of physical fitness level on the motor skill level of students of MTs Negeri 1 Banyumas, F-count of 0.021 < 0.05; (6) the influence of physical activity of sports and physical fitness level on the motor level of students of MTs Negeri 1 Banyumas, F-count of 0.025 < 0.05.